2022
DOI: 10.3390/su141710527
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and the Social Representation of the COVID-19 Pandemic: A Missing Link

Abstract: The COVID-19 pandemic highlighted the importance for countries to preserve a sustainable health system. Unfortunately, the emergency nature of the COVID-19 pandemic has led to economic and social disasters, putting global health at risk. Thus, through the Social Representation Theory, our aim is to replicate a previous study carried out in Brazil in mid-2020 on how Brazilian society has perceived the significance of the COVID-19 pandemic in order to investigate whether this perception changed almost a year aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The focus of this research in Brazil is due to the fact that this country has been significantly affected by the COVID-19 pandemic, with a large number of deaths and an alarming economic crisis caused by the imposed lockdown [29,30]. Moreover, Brazil is also a prominent emerging country, being a BRIC member and having an important role in the global food supply.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this research in Brazil is due to the fact that this country has been significantly affected by the COVID-19 pandemic, with a large number of deaths and an alarming economic crisis caused by the imposed lockdown [29,30]. Moreover, Brazil is also a prominent emerging country, being a BRIC member and having an important role in the global food supply.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found Asian populations to be more likely to wear masks in public than white populations (Trevas et al, 2023), and shoppers in urban or suburban areas are four times more likely to wear masks than shoppers in rural areas (Haischer et al, 2020). Indeed, Recent studies have indicated that attitudes and actions towards mask-wearing vary signi cantly among groups with different cultural backgrounds, education levels, or socioeconomic levels, even under the same external conditions, information, or policies (Joia, Michelotto & Lorenzo, 2022). For instance, in collectivist cultures, wearing a mask is often viewed as a civic responsibility to protect the community, leading to higher rates of mask use.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted with Brazilians showed that the genesis of the social representations of the novel ISSN (Digital): 2223-7666 Liberabit, 2022, 28(2), e617 (julio -diciembre) coronavirus is marked by concerns related to its dissemination, psychosocial implications (collective concern about the prevention of COVID-19 and prophylactic care) and affective issues (uncertainty, feelings of fear and despair) (Do Bú et al, 2020). Studies developed by Joia et al (2022) pointed out that politics and government, social distancing, death, and fear made up the central number of social representations of the pandemic among the Brazilians.…”
Section: Introductionmentioning
confidence: 99%